MENINGKATKAN PEMAHAMAN SANITASI-GIZI SEIMBANG ANAK ORANG TUA MELALUI EDUKASI PARTISIPATIF PAUD CEMPAKA 1 - Zidni Kamalillah; Gundara, Aris; Sinta, Dewi; Rohayati, Ikeu; Sabdaripa, Isma; Bauti, Eni (Paradigma Mandiri : Jurnal Pengabdian Kepada Masyarakat, 2025)
Early childhood health is an important foundation in supporting optimal growth and development, thus requiring special attention in terms of sanitation and balanced nutrition. This study aims to describe the process and outcomes of implementing sanitation education and balanced nutrition for early childhood at PAUD Cempaka 1. The research method used is qualitative with a descriptive approach, where data was collected through observation, interviews, and documentation during the activity. The activity was conducted on August 19, 2025, involving early childhood children and their parents. The series of activities included presenting materials using PowerPoint, hands-on practice in cutting nails, singing a handwashing song as an enjoyable learning tool, and simulating proper handwashing according to the six correct steps. Additionally, simple information about balanced nutrition was presented using a food pyramid diagram and examples of daily menus that were easy for both children and parents to understand. Research findings indicate that children were able to mimic the correct handwashing steps, showed enthusiasm in practicing personal hygiene, and gained a better understanding of the importance of maintaining health. Parents also gained additional insights into creating balanced meal plans at home. Thus, education based on hands-on practice and engaging material delivery proved effective in increasing children's and parents' awareness of clean and healthy living behaviors (PHBS). This activity is hoped to be the first step in fostering positive, sustainable habits in maintaining the health of young children.